Social skills, group cohesiveness, and social adjustment among santri - Vike Nur Aziza; Effy Wardati Maryam (Program Studi bimbingan Konseling PPs UNM Makassar, 2023)
This study aims to examine the relationship between social skills, group cohesiveness, and social adjustment among santri at Burhanul Hidayah. The study used a quantitative correlational design. The data were collected using the social skill scale with the reliability value of 0.824, the group cohesiveness scale with the reliability value of 0.900, and the social adjustment scale with the reliability value of 0.850. Based on the results of the multiple regression analysis conducted on 203 subjects, there is a relationship between social skills, group cohesiveness, and social adjustment with the significance value of 0.000 < 0.05, indicating that there is a relationship between social skills, group cohesiveness, and social adjustment among santri.